2023
DOI: 10.1371/journal.pcbi.1010307
|View full text |Cite
|
Sign up to set email alerts
|

A unitary model of auditory frequency change perception

Abstract: Changes in the frequency content of sounds over time are arguably the most basic form of information about the behavior of sound-emitting objects. In perceptual studies, such changes have mostly been investigated separately, as aspects of either pitch or timbre. Here, we propose a unitary account of “up” and “down” subjective judgments of frequency change, based on a model combining auditory correlates of acoustic cues in a sound-specific and listener-specific manner. To do so, we introduce a generalized versi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…More generally, listeners can group nearby frequencies into auditory objects, which strongly influences the perception of rising and falling pitch (13). Likewise, the perception of continuity with rising and falling tones is also consistent with tracking auditory objects (14), and psychophysical studies of frequency change detection have tended to use isolated frequencies or persistent sound spectra in which auditory object tracking is possible (15)(16)(17)(18). Studies also show that pitch change discrimination can occur over seconds, suggestive of object tracking (19).…”
Section: Introductionmentioning
confidence: 98%
“…More generally, listeners can group nearby frequencies into auditory objects, which strongly influences the perception of rising and falling pitch (13). Likewise, the perception of continuity with rising and falling tones is also consistent with tracking auditory objects (14), and psychophysical studies of frequency change detection have tended to use isolated frequencies or persistent sound spectra in which auditory object tracking is possible (15)(16)(17)(18). Studies also show that pitch change discrimination can occur over seconds, suggestive of object tracking (19).…”
Section: Introductionmentioning
confidence: 98%
“…This manipulation induced the illusory perception of shifts in timbral brightness analogous to the shifts in pitch induced by the classic Shepard tone. In a follow-up study (Siedenburg et al, 2023), the same Shepard tone variations associated with pitch (shifting spectral fine structure, SFS) and timbral brightness (shifting spectral envelope, SE) were again compared in conditions where both SFS and SE shifts were applied simultaneously in either a synergistic or antagonistic manner (same or opposite directions). Behavioral results showed that the two direction changes were very rarely perceived concurrently, and that the stronger cue did not correlate with the component shifted (SFS or SE), but instead with the nature of the sound itself.…”
Section: Introductionmentioning
confidence: 99%